Pre-Service Science Teachers' Beliefs About Creativity at School: A Study in the Hispanic Context - Leidy Dahiana Rios-Atehortua; Tarcilo Torres-Valois; Joan Josep Solaz-Portolés; Vicente Sanjosé (MDPI AG, 2024)
The present study examines the beliefs of pre-service science teachers on creativity in science teaching and learning and identifies factors in the school environment that, in their view, can influence students' creativity. A total of 152 Colombian prospective science teachers participated in this study. A questionnaire, with an open and a closed part, was administered to participants. Descriptive and inferential statistical analysis of the qualitative and quantitative data collected was carried out. The results revealed that (a) the concept of creativity held by the participants was incomplete and significantly diverged from expert definitions; (b) they viewed creativity as a universal potential that can be nurtured within the school system; (c) the ability to identify problems and ask challenging questions was rarely selected as a creative personality trait; (d) they demonstrated unclear ideas about the relationship between creativity and intelligence and the role of prior knowledge in students' creativity; and (e) the subject or curricular domain was seen as an important factor influencing students' creativity. From all this, it could be concluded that Colombian future science teachers exhibited flawed concepts of creativity based on poorly articulated beliefs, which is consistent with findings in other international studies.